Attitudes of Students in a "Student-Centred" High School - Knowles, Donald W.; Henly-Lewis, Jack (Canadian Journal of Counselling and Psychotherapy, 1972)
Attitudes of 437 students toward school were studied to test hypothesized superiority for students attending a "student-centered" secondary school in British Columbia. Comparisons were made with students attending two more-conventional schools in comparable socioeconomic areas in B.C. Attitudes were measured by a modification of a 36-item scale developed by Weaver (1959). Scores for students at the "student-centered" school were significantly greater (p < .05) than for students at other schools. Demographic variables such as school program and sex were associated with differences in attitude scores but the relative advantage of the "student-centered" school was maintained through all comparisons.